Are Social Media Users Blindly Following Influencers’ Recommendations on Investing? - Dalimunthe, Zuliani; Chairunnisa, Ananda; Triono, Rachmadi Agus (The Indonesian Capital Market Review, 2023)
Previous studies show that general information shared by an influencer through social media has been received without sufficient validity testing. However, hardly any study has evaluated whether a stock recommendation by a social media influencer will also be followed blindly. This study evaluates the impact of the credibility of stock influencers on investors’ intention to invest in recommended stocks and whether the relationship can be explained by the perception that the influencer has inside infor- mation or is solely due to fear of missing out (FoMO). This study uses primary data from investors in the Indonesian model market. We collected 135 valid data points and found that a social media influencer’s credibility can explain why an investor intends to invest based on those recommenda- tions. Furthermore, we found that FoMO is a more significant explanation than the perception that the influencer holds a piece of inside information.